Adaptations in golf swing performance following 16-week strength training intervention in elite golfers - Johansen, M.; Aagaard, P.; Bishop, C.; Kvorning, T.; Gejl, K. D.; Bojsen-Møller, J. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction Clubhead speed (CHS) and driving distance are key determinants of elite golf performance, yet evidence from elite cohorts remains limited. This study examined whether a 16-week progressive heavy-resistance training program could improve golf swing performance in elite golfers.